AGRICULTURAL LAND PROTECTION AS A RESULT OF LAND RESOURCES CONSERVATION AND DIGITALIZATION - Ro'zimurodov Bobomurod (Western European Studies, 2025)
The article is devoted to the study of the importance of land resources conservation and digitization technologies in the protection of agricultural lands. The effectiveness of digital technologies in precise control of land areas, monitoring soil fertility and preventing illegal encroachment is analyzed. Also, digitalization projects currently being implemented in the Republic of Uzbekistan, their advantages and development prospects are considered. The article presents national and international experience in the protection of land resources, as well as promising recommendations
Keywords: land resources; agricultural lands; digitization